An Analysis of Students’ English Oral Communication of English Educational Department, PGRI University of Banyuwangi - Ratna Ferdian Sari; Wageyono; Wulan Wangi (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2020)
The objective of this research is to analyze the students’ oral communication in English of the sixth semester students of English Educational Department PGRI University of Banyuwangi in the Academic Year 2018/2019. This research is a descriptive quantitative. The respondents were the sixth semester students of English Educational Department PGRI University of Banyuwangi. The data were taken by using speaking test. The data of speaking test were analyzed by using percentage formula. The result of the data analysis was students’ problem based on grammar, pronunciation and fluency. Based on the data analyzed by using percentage formula, the first indicator is grammar. The students got the percentage scores about 33,78%. Based on the interval range scores, the percentage of students’ grammar scores was categorized as good. The second indicator is pronunciation. The students got the percentage scores about 33,43%. Based onthe interval range scores, the percentage of students’ pronunciationwas categorized as good. Then, the last indicator is fluency. The students got the percentage scores about 32,78%. From the interval range scores, the percentage of students’ fluency wascategorizedas good.